Delayed reward discounting and addictive behavior: a meta-analysis - MacKillop, James (2011)
RATIONALE: Delayed reward discounting (DRD) is a behavioral economic index of impulsivity and numerous studies have examined DRD in relation to addictive behavior. To synthesize the findings across the literature, the current review is a meta-analysis of studies comparing DRD between criterion groups exhibiting addictive behavior and control groups. OBJECTIVES: The meta-analysis sought to characterize the overall patterns of findings, systematic variability by sample and study type, and possible small study (publication) bias. METHODS: Literature reviews identified 310 candidate articles from which 46 studies reporting 64 comparisons were identified (total N=56,013). RESULTS: From the total comparisons identified, a small magnitude effect was evident (d=.15; p<.00001) with very high heterogeneity of effect size. Based on systematic observed differences, large studies assessing DRD with a small number of self-report items were removed and an analysis of 57 comparisons (n=3,329) using equivalent methods and exhibiting acceptable heterogeneity revealed a medium magnitude effect (d=.58; p<.00001). Further analyses revealed significantly larger effect sizes for studies using clinical samples (d=.61) compared with studies using nonclinical samples (d=.45). Indices of small study bias among the various comparisons suggested varying levels of influence by unpublished findings, ranging from minimal to moderate. CONCLUSIONS: These results provide strong evidence of greater DRD in individuals exhibiting addictive behavior in general and particularly in individuals who meet criteria for an addictive disorder. Implications for the assessment of DRD and research priorities are discussed.